A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants - Booher, Douglas B.; Prebus, Matthew; Lubertazzi, David (Zootaxa, 2019)
In this study, we revise two groups of cryptic leaf litter ants, the Strumigenys nitens and Strumigenys simulans species groups. These two groups are restricted to the Greater Antilles and the Bahamas. We redefine the species groups, provide a key for the five species in the S. nitens group, and differentiate the two species in the S. simulans group. Four new species are described: Strumigenys caiman sp. nov., S. economoi sp. nov., S. hubbewatyorum sp. nov., and S. zemi sp. nov. We review and provide a key for the Strumigenys fauna of Hispaniola, which comprises the two endemic species S. economoi and S. zemi, six more broadly distributed Neotropical species, and three pan-tropical “tramp” species.